PRKAG2 and PRKAG3 genes in patients with Wolff-Parkinson-White syndrome: a literature review - Yu. A. Tolstokorova; S. Yu. Nikulina; A. A. Chernova; V. N. Maksimov; Ya. A. Makarov (Российский кардиологический журнал, 2023)
Wolff-Parkinson-White syndrome (WPW) is a syndrome with early ventricular excitation due to the abnormal electrical conduction through an accessory atrioventricular pathway, and is usually accompanied by supraventricular tachycardia. There is a proven genetic component in the development of this syndrome. This review presents current literature data on the association of nucleotide sequence variants of the PRKAG2 and PRKAG3 genes in patients with WPW.